Daclatasvir/peginterferon lambda‐1a/ribavirin in patients with chronic HCV infection and haemophilia who are treatment naïve or prior relapsers to peginterferon alfa‐2a/ribavirin. (24th June 2016) - Santagostino, E.; Pol, S.; Olveira, A.; Reesink, H. W.; van Erpecum, K.; Bogomolov, P.; Xu, D.; Critelli, L.; Srinivasan, S.; Cooney, E.
Abstract : Aim: This study explores the potential role of a novel interferon‐containing regimen for treatment of patients with chronic hepatitis C (CHC) and underlying haemophilia. Methods: This trial (NCT01741545) was an open‐label, non‐randomized phase 3 study, which included adult haemophiliacs with hepatitis C virus (HCV). Patients with HCV genotypes (GT)‐2 or ‐3 were treated with Lambda‐IFN/ribavirin (RBV)/daclatasvir (DCV) for 12 weeks (cohort A). Patients with HCV GT‐1b or ‐4 were treated with Lambda‐IFN/RBV/DCV for 12 weeks, followed by Lambda‐IFN/RBV for an additional 12 weeks (cohort B). The primary endpoint was the proportion of patients with a sustained virologic response at post‐treatment follow‐up week 12 (SVR12). Clinical development of Lambda‐IFN was discontinued during this trial leading to study termination before a 24‐week post‐treatment follow‐up was obtained for all participants. Results: Overall, 51 patients were treated (cohort A, n = 12; cohort B, n = 39). The proportion of patients achieving SVR12 was 92% in cohort A and 90% in cohort B. Therapy was generally well tolerated. The most common adverse events (AEs) were related to elevations in serum transaminases and/or bilirubin. Five serious AEs, four discontinuations due to AEs, and no deaths were reported. The rate of grade 3–4 bilirubin elevations was 17–18% across cohorts. Conclusion: Lambda‐IFN/RBV/DCV treatment demonstrated a high SVR rate and was generally well tolerated with a safety profile consistent with expectations for this special patient population. This study supports use of DCV as part of a combination treatment regimen for haemophiliacs with CHC.